The Management of Pusong Reservoir, Lhokseumawe City, Based on the Suspended Sediment Discharge - Anggi Lanari Lubis; Zulkifli Nasution; Mukhlis Mukhlis (Tunas Geografi, 2023)
The city of Lhokseumawe often experiences flooding or stagnant rainwater. The Pusong Reservoir that was built could have been ineffective in overcoming the flooding problem due to siltation in the reservoir. Therefore, this study aims to review and recommend the management of the Pusong Reservoir based on suspended sediment discharge which is expected to overcome the silting problem of the reservoir. The sampling method was carried out by determining the stations for sampling based on the environmental baseline in determining the six reservation stations. Samples were analyzed for suspended sediment concentration, turbidity, and incoming sediment discharge. Analysis of suspended sediment concentrations ranged from 9.3 - 50.0 ppm, turbidity ranged from 2.17 - 14.42 NTU, and the incoming suspended sediment discharge was 0.00 - 6946.56 kg/day. Based on the analysis of suspended sediment discharge that enters the reservoir, it is necessary to control sediment transport to prevent siltation does not occur in the Pusong Reservoir. The management of the sediment transport control includes sediment traps, vegetative systems, and Spoil Bank Resulting from Sediment Dredging.Keywords:Â Â Suspended Sediment, Management, Pusong Reservoir, Turbidity